Serum immune complexes in cattle with parasitic infections - BARI, A M S; TALUKDER, M J R (The Indian Journal of Animal Sciences, 2013)
Total serum immunoglobulins and circulatinf soluble immune complexes were assessed in cattle affected with naturally occurring gastro- ubtestinal parasitic diseases. Newborn calves and parasite eggs free sera were used as control. Total serum immunoglobuling were measured by single redial immunodiffusion test. Immune complexes were prepared from sera using 2.5% polyethylene glycol. Parasite infected animals had significantly increased level of immunoglobulins and circulating immune complexes compared to Control animals(P